2019
DOI: 10.1002/hep.30411
|View full text |Cite
|
Sign up to set email alerts
|

Thioesterase Superfamily Member 2 Promotes Hepatic VLDL Secretion by Channeling Fatty Acids Into Triglyceride Biosynthesis

Abstract: In nonalcoholic fatty liver disease (NAFLD), triglycerides accumulate within the liver because the rates of fatty acid accrual by uptake from plasma and de novo synthesis exceed elimination by mitochondrial oxidation and secretion as very low‐density lipoprotein (VLDL) triglycerides. Thioesterase superfamily member 2 (Them2) is an acyl‐coenzyme A (CoA) thioesterase that catalyzes the hydrolysis of fatty acyl‐CoAs into free fatty acids plus CoASH. Them2 is highly expressed in the liver, as well as other oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…(5)(6)(7)(8)(9) Whereas the perpetual actions of 26 Acs and 15 Acot family members maintain lipid homeostasis in health, we have shown that obesity-induced activation of Acots, in response to excess fatty acids, can instead traffic excess acyl-CoA toward lipotoxic pathways, such as increased accumulation of saturated phospholipids and VLDL secretion. (8,9) In the current study, we demonstrate that hepatic Acot9 (synonym: mt-Act48, mitochondrial Acot of 48 kDa) expression increases in the setting of NAFLD in mice and patients with obesity. Despite exhibiting broad substrate specificity in vitro, Acot9 is a mitochondrial protein that is enriched in many oxidative tissues and represents the main short-chain Acot within the mitochondria.…”
Section: See Editorial On Page 797mentioning
confidence: 89%
“…(5)(6)(7)(8)(9) Whereas the perpetual actions of 26 Acs and 15 Acot family members maintain lipid homeostasis in health, we have shown that obesity-induced activation of Acots, in response to excess fatty acids, can instead traffic excess acyl-CoA toward lipotoxic pathways, such as increased accumulation of saturated phospholipids and VLDL secretion. (8,9) In the current study, we demonstrate that hepatic Acot9 (synonym: mt-Act48, mitochondrial Acot of 48 kDa) expression increases in the setting of NAFLD in mice and patients with obesity. Despite exhibiting broad substrate specificity in vitro, Acot9 is a mitochondrial protein that is enriched in many oxidative tissues and represents the main short-chain Acot within the mitochondria.…”
Section: See Editorial On Page 797mentioning
confidence: 89%
“…Equal volumes of plasma were pooled from three mice and lipoproteins were fractionated by fast protein liquid chromatography (ÄKTA pure FPLC system, GE Healthcare, Pittsburgh, PA, USA) and triglyceride and cholesterol in fractions quantified with reagent kits (Wako Diagnostics, Mountain View, CA). 68,69 Liver histology and quantification (CF and MP), using the NAS system from NASH-CRN. 39 Steatosis grade (0 :< 5%, 1: 5-33%, 2:…”
Section: Micementioning
confidence: 99%
“…Moreover, PCTP, upon complexing with PC, binds and enhances the enzymatic activity of the thioesterase superfamily member 2 (Them2), a mitochondria-associated long-chain acyl-CoA thioesterase. Them2 is also highly expressed in the liver and plays a key role in the rerouting of fatty acids from β-oxidation to glycerolipid biosynthesis [32]. Therefore, induction of PCTP by VDR could favor Them2 activity and hence the redirection of fatty acids toward TG synthesis.…”
Section: Discussionmentioning
confidence: 99%